Applicability of Wu's criterion for brittle–ductile transition of ethylene/1‐octene copolymer toughened polyamide 6. Issue 2 (11th May 2012) - Hu, Yuexin; Feng, Yulin; Jiang, Yang; Yin, Jinghua; Jiang, Wei
Abstract The brittle–ductile transition of ethylene/1‐octene copolymer (POE) toughened polyamide 6 (PA6) was studied at various temperatures. The experimental results show that the critical interparticle distance (IDc) is independent of the POE content, and the POE particle size at lower temperatures, that is, the temperature is much lower than the brittle–ductile transition temperature (T<alternatives> BDm</alternatives>) of PA6. At higher temperatures, however, especially temperatures close to the T<alternatives> BDm</alternatives>, the IDc depends on the POE particle size. This indicates that Wu's criterion for rubber toughening, specifically that "the IDc is a material property of the matrix, independent of rubber volume fraction and particle size, " is inapplicable at higher temperatures for the brittle–ductile transition of the POE toughened PA6. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013